CORRELATION BETWEEN THE ACCURACY OF MEDICAL TERMINOLOGY AND DIAGNOSTIC CODES FOR RESPIRATORY CASES IN HOSPITAL INPATIENTS - Utami, Yeni Tri; Wariyanti , Astri sri; Susilowati , Sheilla (LPPM Universitas Duta Bangsa Surakarta, 2023)
Accuracy of writing terminology medical necessary to get accurate diagnosis code. Based on results studies introduction to document record medical patient take care Inpatient diagnosis of respiratory cases carried out at Mitra Pedan General Hospital was found to be 60% inaccurate medical terminology and 40% diagnostic code inaccuracies. This research aims to determine the relationship between accuracy in writing medical terminology and accuracy respiratory case diagnosis code for the patient take care stay. Deep method study This namely analytics with a retrospective approach. Amount population 530 documents with sample a total of 229 documents use proportionate stratified random sampling technique. Research instruments include observation guidelines, interview guidelines, checklists, and ICD – 10. Data management by editing, coding, classification, tabulation, cleaning, and data presentation. Analysis using univariate and bivariate. Accuracy writing diagnoses in respiratory cases was more than 140 documents (61%). big rather than inaccuracy as many as 89 documents (39%). For accuracy accurate respiratory case diagnosis code more than 195 documents (85%). big than inaccuracy as many as 34 documents (15%). Data is processed with the Chi-Square statistical test using SPSS, the p value is = 0.149 so p> 0.05. In conclusion namely H0 accepted and Ha rejected, meaning that there is no connection between accuracy of writing medical terminology with accuracy of respiratory case diagnosis codes at Mitra Pedan General Hospital in 2022. This because in handle inaccuracy writing medical terminology, coding officers will confirm directly with doctor so that the resulting diagnosis code still accurate.